Social Theory at Work - Bellemare, Guy (Relations industrielles / Industrial Relations, 2008)
The article reviews the book, "Social Theory at Work," edited by Marek Korczynski, Randy Hodson and Paul K. Edwards.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z